2022
DOI: 10.1177/09697330211035498
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning in dementia care: Wants, beliefs, and insight

Abstract: Background: Advance care planning gives patients and their family members the possibility to consider and make decisions regarding future care and medical procedures. Aim: To explore the view of people in the early stage of dementia on planning for future care. Research design: The study is a qualitative interview study with a semistructured interview guide. The data were analyzed according to the Qualitative Analysis Guide of Leuven. Participants and research context: Dementia nurses assisted in the recruitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…26,43,44 Dickinson et al. 22 noted that life-long conversations led to a confidence in unspoken knowledge to help inform future decision-making. However, according to research, family caregivers may lack full comprehension of what people with dementia see as important and how it relates to care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,43,44 Dickinson et al. 22 noted that life-long conversations led to a confidence in unspoken knowledge to help inform future decision-making. However, according to research, family caregivers may lack full comprehension of what people with dementia see as important and how it relates to care.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] In the early stage of dementia, a person might already struggle to imagine what the future might hold and to plan for coming care needs. [19][20][21][22] The progressive loss of abilities leads to a vulnerability that becomes total and extraordinary as it is situated in all dimensions of the being. 23,24 ACP for people with dementia has received attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it should involve multiple members of the multidisciplinary team (MDT), but most importantly the patient and their family and friends. Moreover, a diagnosis of dementia can be very distressing for the patient, so an ACP has the potential of empowering the patients leading to greater peace of mind [8]. In fact, a Cochrane review carried out by Walsh SC, et al [9], concluded that palliative care at end of life and ACP in dementia management has the potential to improve the patient's quality of life and improve concordance of care [9].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it might cause more anxiety if done at the time of diagnosis which is already distressing in itself. As a result, certain patients might be reluctant to have such conversations [8]. Moreover, reluctance of these discussions are also effected by cultural aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation